Indonesia : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report is part of a joint initiative of the World Bank and IMF to prepare Reports on the Observance of Standards and Codes (ROSC). The ROSC Accounting and Auditing review for Indonesia mainly focuses on the strengths and weaknesses of the accounting and auditing environment that influences the quality of corporate financial reporting. It involves both a review of mandatory requirements and actual practices. The reference points of international standards used in this report are International Financial Reporting Standards (IFRS) International Standards on Auditing (ISA) and international experience and good practice in the field of accounting and auditing regulation. The methodology used to conduct the analytical work for preparing this report includes application of the ROSC Accounting and Auditing diagnostic review. Developed by the World Bank, the diagnostic template was complemented by a comprehensive due diligence exercise. The World Bank ROSC team met with key stakeholders involved in accounting and auditing and corporate reporting in Indonesia. Also, several discussion forums were held with groups of preparers and auditors of financial statements, investors, and financial analysts.